The relationship between eosinophilia and slow coronary flow - Altas Y; Kurtoglu E; Yaylak B; Baysal E; Ucaman B; Ugurlu HM; Karahan MZ; Altintas B; Adiyaman MS; Kaya İ; Erdolu U; Ozen K; et al. (Dove Medical Press, 2015)
Yakup Altas,1 Ertugrul Kurtoglu,2 Baris Yaylak,1 Erkan Baysal,1 Berzal Ucaman,1 Hasan Murat Ugurlu,1 Mehmet Zülkif Karahan,1 Bernas Altintas,1 Mehmet Sahin Adiyaman,1 İlyas Kaya,1 Umut Erdolu,1 Kaya Ozen,1 Cayan Cakir,3 Utkan Sevuk4 1Department of Cardiology, Diyarbakir Gazi Yasargil Education and Research Hospital, 2Department of Cardiology, Malatya State Hospital, Malatya, 3Department of Cardiology, Memorial Diyarbakir Hospital, 4Department of Cardiovascular Surgery, Diyarbakir Gazi Yasargil Education and Research Hospital, Diyarbakir,Turkey Aim: The pathophysiology of slow coronary flow (SCF) involves atherosclerosis, small vessel dysfunction, platelet function disorders, and inflammation. It has been known that eosinophils also play a significant role in inflammation, vasoconstriction, thrombosis, and endothelial dysfunction. We propose to evaluate the relationship between eosinophilia and SCF. Methods: All patients who underwent coronary angiography between January 2011 and December 2013 were screened retrospectively. Of 6,832 patients, 102 patients with SCF (66 males, mean age 52.2±11.7 years) and 77 control subjects with normal coronary angiography (50 males, mean age 50.7±8.1 years) were detected. Baseline characteristics, hematological test results, and biochemical test results were obtained from the hospital database. Results: Baseline characteristics of the study groups were comparable between groups. There was no significant difference between groups regarding leukocyte count, paletelet count, and mean platelet volume. However, patients with SCF had a higher eosinophil count than the controls (0.24±0.17×103/µL vs 0.16±0.15×103/µL, P=0.002). In addition, eosinophil count was found to be correlated with thrombolysis in myocardial infarction (TIMI) frame count in the SCF group (r=0.3, P<0.01). There was no significant correlation between eosinophil count and the number of coronary arteries showing slow flow. Conclusion: Patients with SCF have higher blood eosinophil count, and this may play an important role in the pathogenesis of SCF. Elevated baseline eosinophil count may indicate the presence of SCF. Keywords: eosinophilia, slow coronary flow, coronary angiography